Ultra-marathon running acutely reduces superficial femoral artery flow-mediated dilation in men and women - King, T. J.; Coates, A. M.; Tremblay, J. C.; Slysz, J. T.; Pignanelli, C.; Petrick, H.; Millar, P. J.; Burr, J. F. (Applied Physiology, Nutrition, and Metabolism, 2018)
A prolonged bout of exercise has been shown to impair conduit artery endothelial function; however, this affect has not been investigated in women. Furthermore, the influence of an ultra- marathon (>42.2 km run) on endothelial function in both men and women is unknown. The purpose of this study was to investigate the impact of prolonged trail running on superficial femoral artery flow-mediated dilation (FMD, a measure of endothelial function) among men and women. Nineteen (9F, 10M) distance runners competing in the Sulphur Springs 50 km trail race were assessed for FMD and VO2max <3 weeks prior to the race, and FMD post-race (mean time post-race: 77±26 minutes). Mean race duration was 389±113 minutes. Shear rate (stimulus for FMD) was significantly greater post-race (p=0.02), but FMD was reduced post-race (pre: 4.8±2.5%, post: 2.7±1.7%, p=0.001). The FMD response was not different between men and women (men pre: 4.1±1.7%, post: 2.3±1.1%; women pre: 5.5±3.0%, post: 3.2±2.1%, p=0.7). Change in FMD did not correlate with a change in baseline artery diameter (p=0.9), change in shear rate (p=0.8), VO2max (p=0. 9), training volume (p=0.6), race finishing time (p=0.8), or time between race completion and testing (p=0.5). In conclusion, 50km ultra-marathon running acutely reduces superficial femoral artery FMD in both men and women, despite an increase in post-race shear rate. (Funded by NSERC, CFI.)